2019
DOI: 10.1177/2324709619893548
|View full text |Cite
|
Sign up to set email alerts
|

Primary Central Nervous System Lymphoma in an Immunocompetent Patient Presenting as Multiple Cerebellar Lesions: A Case Report and Review of Literature

Abstract: Primary central nervous system (CNS) lymphoma (PCNSL) is an uncommon extranodal non-Hodgkin lymphoma often presenting as a single brain lesion within the CNS. On histopathological evaluation of PCNSL a positive CD10, which is frequently observed in systemic diffuse large B-cell lymphoma, is present in approximately 10% of PCNSL. We describe a case of CD10-positive PCNSL presenting with multiple posterior fossa enhancing lesions in an immunocompetent older woman with a history of breast cancer successfully trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 19 publications
0
5
1
Order By: Relevance
“…It characteristically demonstrated a homogeneously enhancing mass, with surrounding vasogenic edema and no central necrosis. In the MRS, the manifestations of PCNSL include increased choline (cho) peak, moderately decreased NAA peak, slightly decreased creatine (Cr) peak, as well as a signi cant increase in Lipid and Lac peaks, which indicated neuron damage and increased tumor cell proliferation [9][10][11][12]. In this case, MRI showed invasive lesions distributed in not only supratentorial but also infratentorial sites, which was different from previous reports.…”
Section: Discussioncontrasting
confidence: 55%
“…It characteristically demonstrated a homogeneously enhancing mass, with surrounding vasogenic edema and no central necrosis. In the MRS, the manifestations of PCNSL include increased choline (cho) peak, moderately decreased NAA peak, slightly decreased creatine (Cr) peak, as well as a signi cant increase in Lipid and Lac peaks, which indicated neuron damage and increased tumor cell proliferation [9][10][11][12]. In this case, MRI showed invasive lesions distributed in not only supratentorial but also infratentorial sites, which was different from previous reports.…”
Section: Discussioncontrasting
confidence: 55%
“…The vast majority of patients displayed single cerebellar masses, while just 7 of them had multiple lesions (27%). Two patients received a prior diagnosis of breast cancer [ 17 ], one of atrial myxoma [ 18 ] and the last one of myasthenia gravis [ 19 ]. Complete radiographic studies, clinical examination, and bone marrow biopsies revealed a cerebellum-limited disease in all cases with no other localization, including nodal ones.…”
Section: Resultsmentioning
confidence: 99%
“…However, even in cases where patients show damage to similar neural regions, there can be huge variety in the symptoms presented. A 78-year-old woman with a right cerebellar lesion displayed progressive right-sided ataxia [70] . A 63-year-old man with PCNSL masses in the frontal and parietal cortex who was admitted for left hemiplegia following a seizure [71] .…”
Section: Damage On the Central Nervous Systemmentioning
confidence: 99%
“…Methods of locating and assessing the damage from Grommes [20] 70 F Cerebellum Reduced dexterity and clumsiness Galarza et al [70] 78 F Cerebellum Progressive right sided ataxia Zeng et al [77] 52 F Paraventricular Weakness in limbs and mental decline Haddad et al [78] 72 F Third ventricle Acute memory loss and confusion Khanna et al [74] 85 M Lateral/third ventricle Memory deficits, vision loss, altered sensorium Tan et al [75] 53 M Both eyes Retinal whitening and unilateral visual disturbance Guzzetta et al [76] 82 M Spinal cord Weakness in lower extremities and back pain [56,57] .…”
Section: Damage On the Central Nervous Systemmentioning
confidence: 99%